2008
DOI: 10.1542/peds.2008-1210
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Pediatricians' Opinions on Donation After Cardiac Death: Are the Donors Dead?

Abstract: Most pediatrician respondents were not confident that a donation-after-cardiac-death donor was dead. This suggests that additional debate about the concept of irreversibility applied to donation after cardiac death is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…This despite the fact that compared with adults, pediatric transplantation is often complicated by difficulty in finding size-matched organs. In the United States, where DCDD must be addressed as part of hospital accreditation, pediatric DCDD (pDCDD) has more than doubled in absolute numbers from 2007 to 2013 from 66 to 134 annual donors and represented 14.6% of all pediatric deceased donation in the United States in 2013 (5). In contrast, in Canada, currently, only two centers have active pDCDD protocols, and only one pDCDD donation occurred in 2013, representing 3% of deceased donations (personal correspondence, Canadian Blood Services donation and transplantation data services).…”
Section: E87mentioning
confidence: 99%
See 2 more Smart Citations
“…This despite the fact that compared with adults, pediatric transplantation is often complicated by difficulty in finding size-matched organs. In the United States, where DCDD must be addressed as part of hospital accreditation, pediatric DCDD (pDCDD) has more than doubled in absolute numbers from 2007 to 2013 from 66 to 134 annual donors and represented 14.6% of all pediatric deceased donation in the United States in 2013 (5). In contrast, in Canada, currently, only two centers have active pDCDD protocols, and only one pDCDD donation occurred in 2013, representing 3% of deceased donations (personal correspondence, Canadian Blood Services donation and transplantation data services).…”
Section: E87mentioning
confidence: 99%
“…A large multicenter survey (69) found that 83.4% agreed that surrogates have the right to consent to pDCDD. Physician surveys and HCP focus groups suggest that a majority support the preservation of the DDR (64,66,69). Surveys show confusion by general pediatricians about death determination with concerns about DDR violation (66) and varying levels of agreement by PICU physicians and nurses regarding whether the presence of ECG activity after cessation of circulation prevents death declaration (70).…”
Section: Attitudes Toward Pdcddmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the position that in many circumstances with DCD, the declaration of death might not be as a result of "irreversible cessation of respiratory and circulatory activity". Joffe and co-workers [45] conducted a survey of 147 paediatricians affiliated with a university teaching children's hospital. The survey had four paediatric patient scenarios in which a decision was made to donate organs after 5 min of absent circulation.…”
Section: Ethical and Legal Implicationsmentioning
confidence: 99%
“…ECD is defined as any brain-dead donor aged > 60 years or a donor aged > 50 years with 2 of the following conditions: history of hypertension, terminal serum creatinine level ≥ 1.5 mg/dL (133 μmol/L), or death resulting from a cerebrovascular accident [2] . Evans [3] noted that the number of potential donors of [43][44][45][46][47][48][49][50][51][52][53][54][55] per million of population (pmp) was insufficient to meet the demand and called for REVIEW donation after cardiac death (DCD) in addition to both living-related and living-unrelated kidney donation.…”
Section: Introductionmentioning
confidence: 99%